Pengaruh Penggunaan Smart Board terhadap Hasil Belajar Siswa Sekolah Dasar - Putri Maradila Azzahra; Ani Noviana Rizki; Rahma Gadis Rizqi Salsa Bella; Mailani Dwi Silvia; Dina Amalia (Universitas Palangka Raya, 2025)
The development of digital technology is driving the transformation of learning in elementary schools towards more interactive, collaborative, and meaningful learning. One of the digital media used is the Smart Board, an interactive whiteboard that allows visualization, manipulation, and direct interaction in the learning process. This study aims to examine the effect of Smart Board use on elementary school student learning outcomes and identify supporting factors and challenges in its implementation. The research method used is a literature study by analyzing twenty scientific articles published between 2023 and 2025. Data were analyzed using qualitative descriptive techniques to identify patterns, themes, and key findings. The results show that the consistent use of Smart Boards has a positive impact on improving student learning outcomes, motivation, active participation, and critical thinking skills. The effectiveness of Smart Boards is optimal when integrated with appropriate learning strategies and teacher competencies within the TPACK framework. However, successful implementation is also influenced by teacher readiness, infrastructure availability, and thorough pedagogical planning. These findings confirm that Smart Boards play a role as a digital learning medium that supports in-depth learning.